Management and the dynamics of labour process: study of workplace relations in an oil refinery, Nigeria - Oladeinde, Olusegun Olurotimi (Rhodes University, Faculty of Humanities, Department of Sociology, 2011)
The focus of this thesis is on labour-management relations in the Nigerian National Petroleum Corporation (NNPC), Nigeria. The study explores current managerial practices in the corporation and their effects on the intensification of work, and how the management sought to control workers and the labour process. The study explores the experiences of workers and their perception of managerial practices. Evidence suggests that managerial practices and their impacts on workplace relations in NNPC have become more subtle, with wider implications for workers' experience and the labour process. Using primary data obtained through interviews, participant observation, and documentary sources, the thesis assesses how managerial practices are varieties of controls of labour in which workers' consent is also embedded. This embeddedness of the labour process generates new types of worker subjectivity and identity, with significant implications for labour relations. The study suggests that multiple dimensions of workers' sense-making reflect the structural and subjective dimensions of the labour process. In NNPC, the consequence of managerial practices has been an emergence of a new type of subjectivity; one that has closely identified with the corporate values and is not overtly disposed towards resistance or dissent. While workers consent at NNPC continues to be an outcome of managerial practices, the thesis examined its implications. The thesis seeks to explain the effects of managerial control mechanisms in shaping workers' experience and identity. However, the thesis shows that while workers remain susceptible to these forms of managerial influence, an erasure or closure of oppositions or recalcitrance will not adequately account for workers' identity-formation. The thesis shows that while managerial control remains significant, workers inhabit domains that are 'unmanaged' and 'unmanageable' where 'resistance' and 'misbehaviour' reside. Without a conceptual and empirical interrogation, evidence of normative and mutual benefits of managerial practices or a submissive image of workers will produce images of workers that obscure their covert opposition and resistance. Workers 'collude' with the 'hubris' of management in order to invert and subvert managerial practices and intentions. Through theoretical reconceptualization, the thesis demonstrates the specific dimensions of these inversions and subversions. The thesis therefore seeks to re-insert "worker-agency" back into the analysis of power-relations in the workplace; agency that is not overtly under the absolute grip of managerial control, but with a multiplicity of identities and multilevel manifestations.
Keywords: Nigerian National Petroleum Corporation; Personnel management -- Nigeria; Petroleum industry and trade -- Personnel management -- Nigeria; Performance -- Management -- Nigeria; Industrial relations -- Nigeria; Organizational behavior -- Nigeria; Total quality management -- Nigeria; Labor unions -- Nigeria; Petroleum workers -- Nigeria -- Attitudes